Roads to the past: how to go and not to go backward in time in quantum theories - López, Cristian Ariel (2019)
In this article I shall defend, against the conventional understanding of the matter, that two coherent and tenable approaches to time reversal can be suitably introduced in standard quantum mechanics: an “orthodox” approach that demands time reversal to be represented in terms of an anti-unitary and anti-linear time-reversal operator, and a “heterodox” approach that represents time reversal in terms of a unitary, linear time-reversal operator. The rationale shall be that the orthodox approach in quantum theories assumes a relationalist metaphysics of time, according to which time reversal is nothing but motion reversal. But, when one shifts gears and turn to a substantivalist metaphysics of time the heterodox approach to time reversal in quantum mechanics comes up in a more natural way.